2017
DOI: 10.1002/lary.26813
|View full text |Cite
|
Sign up to set email alerts
|

Tobacco exposure and wound healing in head and neck surgical wounds

Abstract: Objective Smoking impairs wound healing, yet the underlying pathophysiological mechanisms are unclear. We evaluated tobacco-altered healing in head and neck surgery by studying the association between biomarkers and tobacco exposure, as well as cutaneous perfusion by smoking status. Study Design Prospective cohort study, tertiary/academic care center, 2011 to present. Methods Patients who required head and neck surgery were enrolled prospectively. Postsurgical drain fluid was collected 24 hours postoperati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
50
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 35 publications
1
50
0
1
Order By: Relevance
“…The EGF, which is normally secreted by platelets, fibroblasts and macrophages subsequently stimulates keratinocyte migration and proliferation. Some human studies carried out in smokers have documented reduced levels of EGF [9,22,23]. This could explain the delayed reepithelization that was observed in all the tobacco groups but slightly more pronounced in the diabetic groups (TPD and TED) in our study.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The EGF, which is normally secreted by platelets, fibroblasts and macrophages subsequently stimulates keratinocyte migration and proliferation. Some human studies carried out in smokers have documented reduced levels of EGF [9,22,23]. This could explain the delayed reepithelization that was observed in all the tobacco groups but slightly more pronounced in the diabetic groups (TPD and TED) in our study.…”
Section: Discussionsupporting
confidence: 57%
“…Tobacco smoking is said to impede the inflammatory phase of wound healing by reducing cellular chemotaxis, migration and oxidative bacterial phagocytosis [9][10][11][12]. It also retards the proliferative phase of wound healing by reducing fibroblast proliferation and migration with consequent diminished collagen synthesis [13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it was observed that participants who were non-smokers and underwent primary surgical closure were related to decreased length of hospitalization stay. This can be attributed to shorter surgery time, extend of surgery and better wound healing in non-smokers [16]. This study has demonstrated the effectiveness of preoperative nutritional screening and effects of early nutritional interventions in preventing postoperative SSI and decreasing the length of hospitalization stay.…”
Section: Discussionmentioning
confidence: 64%
“…After surgery, the postoperative wound contains an exceedingly complex, physiological network of cells and molecular processes to repair the effects of trauma and heal the wound. Each overlapping phase of healing is essential to the next and to the ultimate outcome, and thus, when disruptions occur, an acute wound may devolve into a chronic wound . Acute wound healing is initiated with the hemostatic phase, during which platelets arrive and a fibrin scaffold is deposited.…”
Section: Discussionmentioning
confidence: 99%
“…The present work was performed in the same manner as previously described by our group . Regulatory approvals were granted by our institution's institutional review board to evaluate this patient population.…”
Section: Methodsmentioning
confidence: 99%